Dynamic Simulation of Doctor Needs in East Java Province By Using iThink - Zabrina, Siti; Nasyifa, Hesti; Febryan, Calvin; Tosida, Tita; Subandi, Kotim; Sugara, Victor Ilyas (Indonesian Operations Research Association (IORA), 2025)
This study compares the calculation of doctor needs in East Java Province using two dynamic simulations, namely iThink and Python. The purpose of this study is to identify differences in results between the two simulation platforms in estimating the need and availability of doctors based on population growth and the number of medical graduates. The methodology used involves modeling population dynamics and the flow of active doctors by considering the inflow of medical students and the WHO ratio. The results of the iThink simulation show an increase in the number of active doctors from 42,000 to 63,793 in 10 years, approaching the ideal WHO ratio, while the Python simulation shows a significant gap between the need and the number of doctors, with the need reaching 257,680 doctors in 2029, but the number of active doctors only reaching 21,686. This difference is due to variations in the methodology and approach of each platform. The conclusion of this study shows the importance of policy interventions to meet the need for doctors in the future and reduce the gap between the need and availability of doctors.